STUDY OF OPAK FAULT CONTROL POINT MOVEMENT IN SGY SEGMENT - Taftazani, Muhammad Iqbal; Parseno, Parseno (GEOID, 2016)
The observation of Opak fault in DIY Province has been done in many times to observe the movement of Opak Fault after 2006 earthquake. This research aims to determine the coordinates in the new epoch (2015) and to determine the movement velocity of Opak fault control point between 2013 and 2015. The research done by GPS/GNSS observations in eight hours with sampling rates 15 second, and GPS/GNSS processing using GAMIT/GLOBK software. The research results shows that there are coordinate differences between 2013, 2014 and 2015 epoch that indicate there is a movement in Opak fault control point with velocity between 0,01 – 0,09 m/yr in horizontal movement and 0,001 – 0,047 m/yr in vertical movement. The movement direction of Opak fault control point is south east except SGY3 point that move to south west. The movement of Opak fault control point is classified by BSN with the extraordinary very slow category.